A spatial genetics approach to inform vector control of tsetse flies (Glossina fuscipes fuscipes) in Northern Uganda. Issue 11 (4th May 2018) - Saarman, Norah; Burak, Mary; Opiro, Robert; Hyseni, Chaz; Echodu, Richard; Dion, Kirstin; Opiyo, Elizabeth A.; Dunn, Augustine W.; Amatulli, Giuseppe; Aksoy, Serap; Caccone, Adalgisa
Abstract: Tsetse flies (genus Glossina ) are the only vector for the parasitic trypanosomes responsible for sleeping sickness and nagana across sub‐Saharan Africa. In Uganda, the tsetse fly Glossina fuscipes fuscipes is responsible for transmission of the parasite in 90% of sleeping sickness cases, and co‐occurrence of both forms of human‐infective trypanosomes makes vector control a priority. We use population genetic data from 38 samples from northern Uganda in a novel methodological pipeline that integrates genetic data, remotely sensed environmental data, and hundreds of field‐survey observations. This methodological pipeline identifies isolated habitat by first identifying environmental parameters correlated with genetic differentiation, second, predicting spatial connectivity using field‐survey observations and the most predictive environmental parameter(s), and third, overlaying the connectivity surface onto a habitat suitability map. Results from this pipeline indicated that net photosynthesis was the strongest predictor of genetic differentiation in G. f. fuscipe s in northern Uganda. The resulting connectivity surface identified a large area of well‐connected habitat in northwestern Uganda, and twenty‐four isolated patches on the northeastern margin of the G. f. fuscipes distribution. We tested this novel methodological pipeline by completing an ad hoc sample and genetic screen of G. f. fuscipes samples from a model‐predicted isolated patch, and evaluated whether the ad hoc sample was in fact as genetically isolated as predicted. Results indicated that genetic isolation of the ad hoc sample was as genetically isolated as predicted, with differentiation well above estimates made in samples from within well‐connected habitat separated by similar geographic distances. This work has important practical implications for the control of tsetse and other disease vectors, because it provides a way to identify isolated populations where it will be safer and easier to implement vector control and that should be prioritized as study sites during the development and improvement of vector control methods. Abstract : Tsetse flies (genus Glossina ) are the only vector for the parasitic trypanosomes responsible for sleeping sickness and nagana across sub‐Saharan Africa. In this study, we integrate high‐resolution satellite imagery, field‐survey results, and genetic data from 38 G. fuscipes fuscipes sampling sites in northern Uganda to identify core areas for management and to improve the G. fuscipes fuscipes habitat suitability model for a particularly high disease risk region of Uganda. Our findings identify twenty‐four isolated habitat patches and improve our understanding of genetic connectivity and thereby contribute data that will help coordinate on‐the‐ground efforts across the large spatial scales relevant for control of this species.